Elective colectomy for treatment of benign colon polyps: National surgical trends, outcomes, and cost analysis - Kaltenbach, Tonya; Martin, Luke; Yu, Jessica; Brooke, Benjamin; Peche, William; Soetikno, Roy; Whooley, Mary; Gawron, Andrew J (Endoscopy International Open, 2025)
Although endoscopic resection is recommended for management of complex benign colon polyps, patients are routinely referred for surgical resection. Little is known about the effects of these elective colectomies on patient outcomes. We sought to determine trends, surgical outcomes, and costs of elective colectomy for benign colon polyps.We performed a retrospective cohort analysis of veterans nationwide using the National Veterans Affairs Surgical Quality Improvement Program (VASQIP) database linked to the national VA Corporate Data Warehouse database. We included all veterans (N = 7,102) undergoing elective colectomy for benign polyps from 2000 to 2015. Outcomes of interest were rates of colectomy, surgical pathology findings, morbidity, mortality, and costs.Colectomy for benign polyps increased significantly from 6% of all colectomies in 2000 to 18% in 2014, and the percent of colectomies for colon cancer decreased from 40% to 31%. The 30-day mortality rate was 1.2% and the complication rate was 19.7%. Based on pathology, 80% of patients (n = 514) underwent right hemicolectomy, mean polyp size was 2.7 cm (± 1.7 cm), and 60.1% of resected polyps were adenomas. Median cost of colectomy was $22,712 for open and $20,697 for laparoscopic colectomy. Costs increased if a complication occurred.Rates of colectomy for benign adenomas significantly increased from 2000 to 2014. Colectomy was associated with significant mortality, morbidity, and cost. Development of strategies to improve endoscopic management of benign large colon neoplasms is urgently needed.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Endoscopic resection (polypectomy, ESD, EMRc, ...); Quality and logistical aspects; Quality management; GI surgery